Effects of Biocrusts on Water Evapotranspiration of Shrub-Grass Ecosystem in Water-Wind Erosion Crisscross Region of Loess Plateau - ZHANG Xudong; YANG Guang; ZHAO Yunge; TAN Taiyu; LIU Ning; YU Shunyao (Shuitu Baochi Xuebao)
[Objective] To determine the effect of biological soil crusts (biocrusts) on water evapotranspiration of the shrub-grass ecosystem. [Methods] The effect of biocrusts on water evapotranspiration of the shrub-grass ecosystem in water-wind erosion crisscross region of Loess Plateau was investigated by using original soil columns of field condition. In the study, the bare soil column was used as control, and three treatments were set up. The three treatments were shrub-grass (single plant shrub-20% grass), shrub-grass-30% biocrusts and shrub-grass-50% biocrusts. [Results] The results showed that after 12 hours of simulated 30 mm precipitation infiltration, water content of 0—20 cm soil layer in the shrub-grass-biotic crust treatment was 15.4% higher than that in the bare soil treatment and 12.8% higher than that in the shrub-grass treatment. Compared with bare soil, soil water evapotranspiration of shrub-grass and shrub-grass with two level of biocrusts’ coverage significantly increased. Among them, soil water evapotranspiration of shrub-grass treatment increased by 120.3% compared to bare soil, while shrub-grass-biocrusts increased by 116.5% on average. Biocrusts reduced soil water evapotranspiration of the shrub-grass ecosystem. Compared with the shrub-grass treatment, soil water evapotranspiration of the shrub-grass-biocrusts decreased by 1.7% on average. The degree of reduction of evapotranspiration was related to the coverage of biocrusts, period and soil depth. Among them, the water evapotranspiration of shrub-grass-50% biocrusts was 13.4% lower than that of shrub-grass-30% biocrusts. The reduction of water evapotranspiration of shrub-grass ecosystem caused by biocrusts was obvious during the first 1~4 days after rain. The reduction of water evapotranspiration of shrub-grass ecosystem caused by biocrusts mainly related to the evapotranspiration of 20—45 cm soil layer. Compared with the shrub-grass treatment, the water evapotranspiration loss of the 0—20 cm soil layer of the shrub-grass-biocrust treatment increased by 14.4% on average, while the water dissipation below 20 cm decreased by 15.5% on average. [Conclusion] Under the condition of 30 mm rainfall, biocrusts reduced the water evapotranspiration of shrub-grass ecosystem, which may beneficial the water deficit of shrub-grass vegetation in the wind-water erosion crisscross area. The study provides a reference for revealing the effect of biocrusts on water evapotranspiration in shrub-grass ecosystems.